Pengaruh Sosialisasi Perpajakan dan Ekstensifikasi Pajak terhadap Penerimaan Pajak Penghasilan Orang Pribadi - suyanto suyanto; Kiftia Yahya (Jurnal Ekonomi Akuntansi dan Manajemen, 2016)
This research aims to test the tax socialization on tax revenues. This research also aims to The tax extension on tax revenues. This research was conducted at the tax office pratama Wonosari.This research was conducted using saturated sample with a sample of 65 respondents sample that may be analyzed about 63 questionnaire. The analysis data method of this research was multiple linear regression. This research was quantitative. The data used in this study are primary data. Based on the results of the analysis indicate that the variable tax socialization and variable tax extension simultaneously and partially on tax revenues individual taxpayers. The predictive ability of the independent variable on the dependent variable showed independent variables were able to explain the dependent variable variation of 43.8% and the rest was explained by other variables. Keywords: the tax socialozation, the tax extension, and tax revenues